Upaya Meningkatkan Kemampuan Motorik Halus melalui Media Tanah Liat di KB Melati Lidah Tanah - Dewi Fitria (Medan Resource Center, 2022)
This study aims to improve children's fine motor skills through activities with clay media in the Melati Lidah Tanah KB. This study uses classroom action research which consists of four stages: planning, implementation, observation and reflection. The subjects in this study were all 17 early childhood children in the Melati Lidah Tanah KB. Data collection techniques were carried out through direct observations of all children of group B KB Melati Tongue Tanah through clay media. Data analysis techniques use descriptive techniques. The results showed that the improvement of children's fine motor skills through activities with clay media from pre-cycle reached 39.70% and in the first cycle it reached 49.63% and in the second cycle it reached 79.4%. conducted at the time of research at KB Melati Lidah Tanah T.A 2020-2021